MEDIATION ROLE OF ORGANIZATIONAL COMMITMENT BETWEEN WORK COMPETENCY AND INCREASED EMPLOYEE PRODUCTIVITY - Sutarman, Asep (Jurnal Aplikasi Manajemen, 2022)
This study analyzes employee competence and organizational commitment to increasing employee productivity as a research sample of 300 respondents. Structural Equation Modeling with AMOS version 20.0 was used to test the hypothesis and the Sobel Test formula to test the mediating role of research. The study results reveal that work competence and organizational commitment partially and significantly affect employee work productivity. The analysis also found that organizational commitment has the greatest influence on increasing employee productivity. Based on the mediation analysis, it was also found that organizational commitment positively mediates the significant effect of work competence on employee productivity. This research can contribute to future research, especially in human resource management and organizational behavior, especially in Indonesia. As a research policy, firm executives are strengthening their commitment to paying attention to employee competency, particularly incompetence and behavior. To strengthen core competencies, the company's leadership must cultivate the firm's core values, and then, in behavioral competence, the company leadership must be able to motivate people so that their work productivity grows.